Genetic And Chemical Variation Of Clinacanthus Nutans From Northern Region Of Peninsular Malaysia - Ismail, Noor Zafirah (2018)
Clinacanthus nutans is a valuable medicinal plant which has gained more attention in the last few years mainly because of its pharmacological properties. Despite this, there is little information available about the genetic and phytochemicals of the plant in different locations. Therefore, the objectives of this study were to identify C. nutans using deoxyribonucleic acid (DNA) barcode loci, evaluate genetic diversity by using 17 primers of ‘random amplified polymorphic deoxyribonucleic acids’ (RAPD), eight primers of ‘inter-simple sequence repeats’ (ISSR) and 136 primers of ‘random amplified microsatellite polymorphisms’ (RAMP) and determine the total flavonoid, phenolic contents, antioxidant activity and phytochemical contents of C. nutans using gas chromatography-mass spectrometry (GC-MS). A total of 80 C. nutans accessions from eight different locations in the northern region of Peninsular Malaysia were harvested. The plant was identified using voucher collection and the sequence of polymerase chain reaction (PCR) products using DNA barcode markers namely matK, rbcL, and trnH-psbA. The PCR product sequence analysis showed that C. nutans was identified and trnH-psbA was chosen as the suitable marker for C. nutans identification. Genomic DNA had successfully amplified ten primers of RAPD, five primers of ISSR and 37 primers of RAMP by using PCR in genetic variation analysis. C. nutans showed low percentage polymorphism at the population level compare to species level.